2010
DOI: 10.1002/pon.1837
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and physical performance and activity of breast cancer patients after adjuvant treatments

Abstract: The QoL of the patients shortly after adjuvant treatments was impaired and the physical performance poor as compared to general population. In particular, depression and fatigue were related to impaired QoL. Physical performance and activity level were the only factors that correlated positively to QoL. Thus, physical exercise could be useful in rehabilitation of cancer survivors, especially for depressed and fatigued patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
66
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 54 publications
8
66
0
5
Order By: Relevance
“…Mediante técnicas conductuales y ejercicio físico, el meta-análisis de Dujits et al (52)(53)(54) . (55) .…”
Section: Revisión De Intervenciones Psicológicas En La Fase Libre De unclassified
“…Mediante técnicas conductuales y ejercicio físico, el meta-análisis de Dujits et al (52)(53)(54) . (55) .…”
Section: Revisión De Intervenciones Psicológicas En La Fase Libre De unclassified
“…[4] Other psychological and emotional side-effects experienced by cancer patients include stress, fear of death, poor body image, low self-esteem, loneliness and a sense of loss of control over life. [2,3] One study [9] found a similar deterioration in fatigue and QoL measures in breast cancer patients shortly after completing adjuvant therapies. QoL impairment was also strongly associated with scores on depression, as well as fatigue.…”
Section: Treatment Effects On Quality Of Lifementioning
confidence: 99%
“…QoL impairment was also strongly associated with scores on depression, as well as fatigue. [9] Despite an inconclusive relationship between psychological distress and cancer survival, a review of available research relating to breast cancer shows that most studies indicate a significant relationship between psychological factors and survival. [10,11] Clinical depression is associated with non-compliance with cancer treatment and reduced survival, emphasising that depression negatively affects the psychological and physical health of many patients.…”
Section: Treatment Effects On Quality Of Lifementioning
confidence: 99%
“…The short-term side effects and long-term reproductive sequelae of cancer treatments on this population are becoming increasingly important. For these survivors, menopausal symptoms and concerns about infertility are common and have a negative impact on quality of life [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%